Mass Production of Large‐Sized, Nonlayered 2D Nanosheets: Their Directed Synthesis by a Rapid "Gel‐Blowing" Strategy, and Applications in Li/Na Storage and Catalysis. Issue 43 (4th September 2018) - Wang, Dong; Zhou, Weiwei; Zhang, Rui; Zeng, Jinjue; Du, Yu; Qi, Shuai; Cong, Chunxiao; Ding, Chunyan; Huang, Xiaoxiao; Wen, Guangwu; Yu, Ting
Abstract: 2D nanomaterials are well suited for energy conversion and storage because of their thickness‐dependent physical and chemical properties. However, current synthetic methods for translating 2D materials from the laboratory to industry cannot integrate both advantages of liquid‐phase method (i.e., solution processibility, homogeneity, and massive production), and gas‐phase method (i.e., high quality and large lateral size). Here, inspired by Chinese Sugar Figure Blowing Art, a rapid "gel‐blowing" strategy is proposed for the mass production of 2D nonlayered nanosheets by thermally expanding the viscous gel precursors within a short time (≈1 min). A wide variety of 2D nanosheets including oxides, carbon, oxides/carbon and metal/carbon composites are synthesized on a large scale and with no impurities. Importantly, this method unifies the merits of both liquid‐phase and gas‐phase syntheses, giving rise to 2D products with high uniformity, nanometer thickness, and large lateral sizes (up to hundreds of micrometers) simultaneously. The success of this strategy highly relies on the speed of "blowing" and control of the amount of reactants. The as‐synthesized nanosheet electrodes manifest excellent electrochemical performance for alkali‐ion batteries and electrocatalysis. This method opens up a new avenue for economical and massive preparation of good‐quality nonlayered 2D nanosheets for energy‐related applications and beyond. Abstract : A rapid "gel‐blowing" strategy for mass production of nonlayered 2D nanosheets is presented. A wide variety of 2D nanosheets including metal oxides, carbon, metal oxides/carbon, and metal/carbon composites are synthesized on a large scale and with no impurities. These 2D nanosheets manifest excellent electrochemical performance as electrodes for rechargeable batteries and electrocatalysis.